The Effectiveness of Kahoot! in Increasing Student Participation and Learning Outcomes in Higher Education - Dian Atmasani; Sutarsi Suhaeb; Nurfauziah; Nur Syamsinar Munir (Information Technology Education Journal, 2025)
The transformation of learning in the digital age encourages the use of interactive media that can increase student engagement and academic achievement. One such medium is Kahoot!, a game-based learning platform designed to facilitate active participation. This study aims to analyze the effect of using Kahoot! on student active participation and learning outcomes. The study was conducted using a quantitative correlational approach, employing multiple linear regression analysis to measure the relationship between the independent variable and the two dependent variables, both partially and simultaneously. The research sample consisted of 60 students from the Electronics Engineering Education Program at the University of Makassar during the spring semester of 2024/2025. The instrument used was a validated closed-ended Likert-scale questionnaire, with reliability tested using Cronbach’s Alpha. The results of the study indicate that the use of Kahoot! significantly influences active participation and student learning outcomes, both partially and simultaneously, contributing 49.4% to both variables. The main contribution of this study is to provide the latest empirical evidence on the effectiveness of integrating gamification technology in higher education in Indonesia, as well as demonstrating that Kahoot! can serve as an innovative strategy in designing more interactive, competitive, and adaptive learning experiences to address the challenges of the digital age.